Pelaksanaan Perjanjian Kerja Sama Pengamanan Objek Vital Antara Kepolisian Resor Bengkulu Dan Bank Bengkulu - Herdian, Rizky; Amancik, Amancik; Jalili, Ismail (Jurnal Multidisiplin Dehasen (MUDE), 2025)
An agreement is an act by which one or more people bind themselves to one or more people in implementing a cooperation agreement for securing vital objects between the Bengkulu Police and Bank Bengkulu, whether the agreement is valid as per Article 1320 of the Civil Code and has been implemented by both parties, the obstacles faced in implementing the cooperation agreement, and the resolution of the dispute if a breach of contract occurs. In the cooperation agreement for securing vital objects between the Bengkulu Police and Bank Bengkulu, it has been implemented by both parties in accordance with the contents of the agreement containing the rights and obligations of the parties, as well as the fulfillment of the valid conditions of the agreement, both subjective and objective conditions, in accordance with Article 1320 of the Civil Code. The obstacles faced in implementing the cooperation agreement are from the underutilization of security facilities such as CCTV, external obstacles, namely the large number of customers at the beginning of the month which causes the security personnel to be overwhelmed. In the agreement, if one party causes a breach of contract due to the agreement, it can be resolved in a non-litigation manner, namely mediation and deliberation, but if it is unsuccessful, the court will take the form of.